KOMUNIKASI PROFETIK SEBAGAI STRATEGI PENDIDIKAN AKHLAK DI YAYASAN KELUARGA BESAR RUQYAH ASWAJA PUSAT GROBOGAN JAWA TENGAH - EKO PURNOMO; NUR SAIDAH (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to analyze prophetic communication as a moral education strategy at the Central Ruqyah Aswaja Family Foundation, to analyze the application of prophetic communication as a moral education strategy at the Ruqyah Aswaja Central Family Foundation, and to analyze prophetic communication strategy as a moral education strategy at the Ruqyah Aswaja Central Family Foundation. . Misunderstanding in communication is a problem that occurs today. These problems include innuendo, insults, degrading the self-esteem of others. Therefore, it is necessary to apply prophetic messages based on moral education. This research is a qualitative type of field research with a phenomenological approach. Data collection techniques using interviews, observation, and documentation. The results of this study show three things. First, prophetic communication as a moral education strategy, namely the values ​​of humanization, liberation, and transcendence. Second, the application of prophetic communication as a moral education strategy can be seen from the implementation of activities or learning, ruqyah training, implementation of ruqyah activities, implementation of lectures, routines (dhikr). The three strategies used in the application of prophetic communication as a moral education strategy using tazkiyatun nafs are takhalli, tahalli and tajalli.